Effect Of Applying The E-Learning Learning Model As A Solution To The Covid-19 Pandemic On Student Learning Outcomes - Abidin, Jainal (JOURNAL OF DIGITAL LEARNING AND DISTANCE EDUCATION, 2024)
The development of science and technology in this era is proliferating. The effect of implementing these regulations resulted in the teaching and learning process that should have been carried out face-to-face becoming network-based learning. The research method used is experimental research, which is a method used to see whether there is a change that occurs after giving treatment to research subjects who are a source of data for researchers. The use of e-learning media is expected to overcome learning barriers. The research aims to improve students' knowledge and learning outcomes. So, when conducting research, it was found that learning with e-learning media had not been able to provide satisfactory results on student learning outcomes, where student learning outcomes did not reach the target KKM value of 75. Many factors influenced this, including not all students having smartphones and low network signal quality.